The Universality of Education for Children with Special Needs in India: Current Status - Sushma Kumari; Gita Jyoti Ojh (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
The Right to education is one of the basic fundamental rights upheld by the constitution of India to every child. Children with special needs face massive challenges in being able to access education equitably due to various reasons viz. a rigid curriculum, non-accessibility, untrained teachers, bullying, and attitudinal issues. The new NEP (National Education Policy) 2020 seems to bring across many progressive steps which when clubbed with the RPWD (Right of Persons with Disabilities) act 2016 offers hope for children with special needs. In this article, we try to examine the various provisions outlined in the new NEP 2020 in the backdrop of RPWD 2016. An understanding of which will lead to predicting the barriers and gaps one can come across in the future during implementation at the ground level. Something which remains a challenge for a country like India with the best policies yet few actions.